2022
DOI: 10.1007/s13346-022-01245-z
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin-modified chitosan nanoparticles for targeted nose-to-brain delivery of proteins

Abstract: Nose-to-brain delivery presents a promising alternative route compared to classical blood–brain barrier passage, especially for the delivery of high molecular weight drugs. In general, macromolecules are rapidly degraded in physiological environment. Therefore, nanoparticulate systems can be used to protect biomolecules from premature degradation. Furthermore, targeting ligands on the surface of nanoparticles are able to improve bioavailability by enhancing cellular uptake due to specific binding and longer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…Application of such NPs to brain tumors has occurred only recently, however, and focus has been on the modification of delivery carriers that utilize the transnasal entry into the brain. For example, Tf‐modified chitosan NPs have been shown to enter the BBB via the nose‐to‐brain pathway and penetrate at a faster rate in the presence of glioma cells (Gabold et al, 2022). Sandbhor et al investigated the potential of employing the noninvasive intranasal pathway to target the DNA methylating agent temozolomide to glioma.…”
Section: Transcytosis In the Nose‐to‐brain Pathwaymentioning
confidence: 99%
“…Application of such NPs to brain tumors has occurred only recently, however, and focus has been on the modification of delivery carriers that utilize the transnasal entry into the brain. For example, Tf‐modified chitosan NPs have been shown to enter the BBB via the nose‐to‐brain pathway and penetrate at a faster rate in the presence of glioma cells (Gabold et al, 2022). Sandbhor et al investigated the potential of employing the noninvasive intranasal pathway to target the DNA methylating agent temozolomide to glioma.…”
Section: Transcytosis In the Nose‐to‐brain Pathwaymentioning
confidence: 99%
“…Polymeric nanoparticles, notably chitosan NPs are the most popular nanocarriers used in nose-to-brain delivery and are at the forefront of neuropharmacological treatments due to their mucoadhesive properties and the ability of CS NPs to open the TJ existing within the nasal epithelial barrier. 153,154 Wilson et al reported the delivery of sitagliptin (SIT) into the brain of rats using SIT-loaded chitosan particles of 188.4 AE 48.1 nm mean size and z = +20.8 mV. 155 Gabold et al studied the passage of b-galactosidase through human nasal epithelial cells (RPMI 2650) using transferrin-decorated chitosan NP carriers.…”
Section: Alternative Non-invasive Delivery Via Nose-to-brain Deliverymentioning
confidence: 99%
“…155 Gabold et al studied the passage of b-galactosidase through human nasal epithelial cells (RPMI 2650) using transferrin-decorated chitosan NP carriers. 153 Readers are referred to the excellent review by Donnelly and Paredes. 154 Galladro-Tolers delivered peptide modified Au NPs IN (Fig.…”
Section: Alternative Non-invasive Delivery Via Nose-to-brain Deliverymentioning
confidence: 99%
“…The outcomes demonstrated a statistically significant rise in drug concentration in the brain and improvements in the mice’s behavior ( p < 0.05) with the developed NPs. Similarly, transferrin chitosan NPs were assessed for their potential to deliver proteins [ 117 ]. This study highlights the advantageous properties of such formulation strategies and suggests that a range of targeted ligands could be attached to their surface while preserving the integrity of the cargo.…”
Section: Nanoparticles For Nose-to-brain Drug Deliverymentioning
confidence: 99%